Delays to essential surgery at four faith based hospitals in rural Sub‐Saharan Africa. Issue 1 (29th December 2021) - Sund, Gregory; Huang, Andrew H.; Mascha, Edward J.; Miburo, Césarie; Machemedze, Solomon; Razafimanantsoa, Mirana; Tankombo, Roger; Brown, James A; Watts, Edward; O'Connor, Zachary
Abstract: Background: Data regarding delays for emergency surgery in Sub‐Saharan Africa is limited. We have therefore decided to undertake an evaluation of delays in patients seeking care, reaching care and receiving care for emergency surgery at four rural faith‐based hospitals in this region over a 3 month period. Methods: This is a cross‐sectional, multi‐center, international study at four rural faith‐based hospitals in Madagascar, Gabon, Cameroon and Burundi. All patients presenting at these hospitals between 10 February and 1 May 2020 for one of the three Bellwether procedures (caesarean delivery, emergency laparotomy, management of open fracture) were to be enrolled in this study. Data was collected in the form of a questionnaire administered to the patient or the patient's caregiver within 24 h of admission to the hospital. Results: After analysis of data for 148 patients, we found that the median [quartiles] delay in seeking care overall was 3.5 [0.5, 17.6] h, in reaching care 7.6 [2.3, 33.6] h and in receiving care 3.6 [1.7, 6.8] h. In 72% (107/148) of cases, the second delay was more than 2 h. Sixty‐five percent of patients who were delayed reported that their delay was because care was sought elsewhere before arrival at one of our Bellwether‐capable sites. Conclusions: Our results suggest that the majority of patients needing emergency surgical care in the rural areas of Sub‐Saharan Africa where our study was conducted are frequently delayed, with the largest delay being in reaching care. Further investigations into the reasons for these delays should be conducted. Abstract : This study looked at the delays to essential surgical care using the Three Delays Framework of the Lancet Commission on Global Surgery. Four rural hospitals in four separate African countries prospectively logged the reasons for delays for three Bellwether procedures. Delays were most notable in reaching a Bellwether‐capable facility.